2009
DOI: 10.17763/haer.79.4.02671846902gl33w
|View full text |Cite
|
Sign up to set email alerts
|

Sin Papeles y Rompiendo Barreras: Latino Students and the Challenges of Persisting in College

Abstract: Undocumented Latino students in higher education represent a resilient, determined,and inspirational group of high achievers who persevere and serve as a model for success. Here, Frances Contreras presents a qualitative case study consisting of twenty semistructured, in-depth interviews with undocumented Latino students in an effort to help readers understand the experiences and challenges facing them in higher education in Washington State. Contreras's research explores the navigational processes these studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 17 publications
3
173
0
1
Order By: Relevance
“…Likewise, positive perceptions of the university environment, as measured by a set of reliable items from the University Environment Scale, were found to positively affect Latina/o students' persistence decisions (Gloria, 1997;Gloria et al, 2005;Gloria & Robinson-Kurpius, 1996). At the same time, qualitative findings suggest discriminatory campus experiences, such as negative interactions with school officials and isolation, were barriers to success for undocumented Latina/o students in Washington (Contreras, 2009). At the same time, qualitative findings suggest discriminatory campus experiences, such as negative interactions with school officials and isolation, were barriers to success for undocumented Latina/o students in Washington (Contreras, 2009).…”
Section: Perceptions Of the Campus Climate/environmentmentioning
confidence: 98%
“…Likewise, positive perceptions of the university environment, as measured by a set of reliable items from the University Environment Scale, were found to positively affect Latina/o students' persistence decisions (Gloria, 1997;Gloria et al, 2005;Gloria & Robinson-Kurpius, 1996). At the same time, qualitative findings suggest discriminatory campus experiences, such as negative interactions with school officials and isolation, were barriers to success for undocumented Latina/o students in Washington (Contreras, 2009). At the same time, qualitative findings suggest discriminatory campus experiences, such as negative interactions with school officials and isolation, were barriers to success for undocumented Latina/o students in Washington (Contreras, 2009).…”
Section: Perceptions Of the Campus Climate/environmentmentioning
confidence: 98%
“…Research has long demonstrated that high educational aspirations positively correlate with educational attainment (Deil-Amen and Turley 2007), and recent studies on undocumented college students suggest that members of this group tend to hold exceptionally high aspirations, in spite of the challenges posed by their legal status (Contreras 2009; Perez and Cortes 2011). Additionally, undocumented students who do attend college appear to benefit from the extensive assistance of mentors, as well as broad networks of support (Enriquez 2011; Gonzales 2011).…”
Section: Immigrant Incorporation and College Persistencementioning
confidence: 99%
“…When they do manage to pursue higher education, they are likely to concentrate in the nation's relatively accessible and comparatively affordable community colleges, which offer vocational training and associates degrees, rather than in more costly 4-year institutions that grant bachelor's degrees (Teranishi, Suarez-Orozco, and Suarez-Orozco 2011). A growing body of scholarship has provided important insights into experiences of undocumented college students in the US (Contreras 2009; Enriquez 2011; Gonzales 2011; Perez and Cortes 2011), yet we still know very little about the persistence and degree completion of undocumented community college students, especially as their experiences compare to those of US citizens and legal permanent residents (LPRs). The problem is twofold: available data on randomly selected college students do not typically identify those who lack legal documentation (Greenman and Hall 2013; Teranishi, Suarez-Orozco, and Suarez-Orozco 2011), while studies of non-randomly selected undocumented students rarely contain comparison samples (for exception, see Dozier 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The most common barrier for undocumented students noted in the literature is that they do not qualify for federal or state financial aid and, depending on the state in which they reside, are required to pay nonresident tuition rates (Contreras, ; Flores, ; Frum, ; Gonzales, ). Nonresident tuition rates are typically two to seven times higher than tuition rates for in‐state residents (Feder, ; Olivas, ).…”
Section: Challenges and Struggles Of Undocumented Studentsmentioning
confidence: 99%